2021
DOI: 10.3390/ijerph18052619
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Effects and Use of Communication Technologies during Home Confinement in the First Wave of the COVID-19 Pandemic in Italy and The Netherlands

Abstract: (1) Background: The COVID-19 pandemic forced people from all around the globe to strongly modify their daily routines, putting a significant strain on the social aspects of daily lives. While the first wave of the pandemic was a very challenging time in all countries, it is still uncertain whether various lockdown intensities and infection rates differed regarding their psychosocial impact. This work therefore aimed to investigate (i) the psychosocial effects of home confinement in two European countries that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
(44 reference statements)
0
10
2
3
Order By: Relevance
“…The difference in the association between work and non-work usage with psychological distress may be due to the fact that being employed is psychologically beneficial by increasing self-reliance [31], whereas non-work VDT usage has little psychological value. During the COVID-19 pandemic, physical distancing makes VDTs a means of social interaction [32], which is proven to be associated with improved physical and psychological health [33]. However, in our study, VDT usage for non-work activities was not associated with psychological distress, and there was a potential negative linear association.…”
Section: Discussioncontrasting
confidence: 69%
“…The difference in the association between work and non-work usage with psychological distress may be due to the fact that being employed is psychologically beneficial by increasing self-reliance [31], whereas non-work VDT usage has little psychological value. During the COVID-19 pandemic, physical distancing makes VDTs a means of social interaction [32], which is proven to be associated with improved physical and psychological health [33]. However, in our study, VDT usage for non-work activities was not associated with psychological distress, and there was a potential negative linear association.…”
Section: Discussioncontrasting
confidence: 69%
“…They clarified that while new ways of working can help workers’ engagement, work-related flow, and connectivity among staff, new ways of working can also increasing the blurring of work–home boundaries, fatigue, and mental demands. Bastoni et al [ 25 ] revealed that the increase in loneliness was associated with the adoption of new digital communication tools, and was significantly higher for individuals who started to adopt at least one new digital communication tool during confinement than for those who did not. In a web-based survey of Spanish households during the spring 2020 lockdown, Cuerdo-Vilches et al [ 26 ] showed that the adequacy of telework environment spaces was insufficient for more than a quarter of the homes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, COVID-19-related home confinement significantly and deleteriously altered sleep quality and PA levels in a large global sample of people ( Trabelsi et al, 2021 ). The study of Bastoni et al (2021) highlights COVID-19 home confinement in Europe significantly impacted psychosocial wellbeing during the first wave of the pandemic, despite different lockdown intensities.…”
Section: Introductionmentioning
confidence: 99%